2007
DOI: 10.1007/s11524-007-9187-1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Violence and Psychological Distress Among Low-income Urban Women

Abstract: In this paper, we examined the association between relationship violence and psychological distress among low-income urban women. Extending prior research, we considered the effects of relationship violence within the context of other chronic stressors that are common in the lives of these women. Using data from the Welfare, Children, and Families project (1999), a probability sample of 2,402 low-income women with children living in low-income neighborhoods in Boston, Chicago, and San Antonio, we predicted psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 45 publications
4
25
0
Order By: Relevance
“…Although investigations typically focus on depression or anxiety as an outcome of relationship violence (Beydoun, Beydoun, Kaufman, Lo, and Zonderman 2012; Coker et al 2002; Hill, Mossakowski, and Angel 2007; Johnson, Giordano, Longmore, and Manning 2014), a number of scholars using nationally representative and clinical samples have found that both stress and depression influence IPV perpetration (Hamberger and Hastings 1986; Straus 1990). These findings highlight that IPV is, at least in part, related to emotional wellbeing (Anderson 2002).…”
Section: Emotional Distress and Intimate Partner Violencementioning
confidence: 99%
“…Although investigations typically focus on depression or anxiety as an outcome of relationship violence (Beydoun, Beydoun, Kaufman, Lo, and Zonderman 2012; Coker et al 2002; Hill, Mossakowski, and Angel 2007; Johnson, Giordano, Longmore, and Manning 2014), a number of scholars using nationally representative and clinical samples have found that both stress and depression influence IPV perpetration (Hamberger and Hastings 1986; Straus 1990). These findings highlight that IPV is, at least in part, related to emotional wellbeing (Anderson 2002).…”
Section: Emotional Distress and Intimate Partner Violencementioning
confidence: 99%
“…Along with the troubles associated with living in disadvantaged neighborhoods, the urban poor are regularly confronted with the trials of financial hardship, substandard housing, relationship violence, and poor health (Hill et al. ; Hill et al. ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…1 forms is experienced at every socioeconomic level, residents of communities with poor economic opportunities and outlooks bear the burden of high rates of structural violence, including racism and discrimination, predatory violence, and relationship violence. [4][5][6] According to the National Crime Victimization Survey, women living in families with the lowest annual household incomes were nearly seven times more likely to be victimized by intimate partners than those living in homes with the highest earnings.…”
Section: Introductionmentioning
confidence: 99%